Penerapan Manajemen Operasional Ritel Untuk Mendukung Pelayanan Konsumen Di Toserba Sunan Drajat Cabang Sedayulawas - Silvi Aulia Putri (Jurnal Manajemen, Ekonomi, Hukum, Kewirausahaan, Kesehatan, Pendidikan dan Informatika, 2026)
This study aims to analyze the implementation of retail operational management in supporting the quality of customer service at Sunan Drajat Department Store, Sedayulawas Branch. The focus of this study is directed at product inventory management, product display arrangement, cashier transaction processes, the implementation of standard operating procedures (SOPs), work coordination, and customer service patterns in daily operational activities. The method in this study uses a descriptive qualitative approach with data collection techniques through interviews, direct observation, and documentation. Data analysis is carried out in stages including data reduction, data presentation, and drawing conclusions to obtain a factual picture of the retail operational conditions. The results show that the implementation of retail operational management has been carried out in a structured manner through the process of receiving goods, checking product quality and expiration, systematic shelf arrangement, and computer-based cashier services. The implementation of standard operating procedures (SOPs) and coordination between employees also support smooth operations and increase customer comfort. Thus, retail operational management plays a vital role in maintaining operational effectiveness and is able to improve the quality of customer service continuously.